Study of the PD-1 expression in lung carcinoma cells and T lymphoblasts by Euglena gracilis water extract - DeVader, Sarah (My University, 2025)
Lung cancer is the leading cause of cancer related deaths in the United States. Natural products are a diverse source of anticancer compounds. Euglena gracilis (E. gracilis) is a unicellular freshwater green alga rich in nutrients that is used as a dietary supplement. It has been studied for its many properties, including anti-inflammatory, antiviral, and antitumoral. We have been investigating the preventative effects of E. gracilis against lung cancer development. Our previous studies demonstrate water extract from E. gracilis (EWE) possesses anti-cancer activity against lung carcinomas and stimulates T-cell cytotoxicity against lung cancer cells. However, it is unknown how EWE directly attenuates the growth of lung carcinoma cells and directly stimulates T cells, and what component(s) within EWE are responsible for these biological effects. In the current study, we investigated the relationship between EWE and the mRNA expression of PD-1 in lung carcinoma cells and T cells. Orally administered EWE in an orthotopic lung cancer syngeneic mouse model was revealed to increase the expression of PD-1 and PD-L1 in tumor-bearing mouse lungs, which was correlated with a decrease in tumor weights in the mice. In vitro, EWE was found to increase the mRNA expression of PD-1 and PD-L1 in both murine Lewis lung carcinoma (LLC) cells and murine splenocytes, and EWE also increased the mRNA expression of PD-1 and granzyme B in human Jurkat T lymphoblasts. Using the EWE-induced stimulation of these proteins as assay tools, the bioactive compound in EWE was purified by FPLC with a size exclusion column. Three specific fractions were found to increase the mRNA expression of PD-1 and PD-L1 in LLC cells and the mRNA expression of PD-1 and granzyme B in Jurkat cells. The FPLC fraction which showed highest bioactivity was further fractionated by C18 reverse phase HPLC. The resulting HPLC fraction that increased the expression of PD-1 in LLC cells was subjected to the structural analysis by liquid chromatography mass spectroscopy and nuclear magnetic resonance, which is currently underway. These results suggest that there is a relationship between the EWE-induced attenuation of lung tumor growth and the EWE-induced increased PD-1 expression, and that EWE treatment may enhance its therapeutic efficacy by stimulating antitumor immunity in lung cancer. The PD-1 stimulator present in EWE was preserved throughout fractionation with FPLC and HPLC in tandem, and, once identified, could provide clear insights into the mechanisms by which EWE achieves these biological effects.
Keywords: Lung cancer; Immune checkpoint inhibitor therapy; PD-1; Euglena gracilis water extract